Role of Water and Defects in Photo‐Oxidative Degradation of Methylammonium Lead Iodide Perovskite. Issue 7 (18th April 2019) - Ouyang, Yixin; Shi, Li; Li, Qiang; Wang, Jinlan
Abstract: Great progress has been made in improving power conversion efficiency of perovskite solar cells (PSCs), and now the pressing issue is the poor stability of organic–inorganic halide perovskites under ambient conditions. Degradation of MAPbI3 induced by light and oxygen is a dominant factor limiting the lifetime of PSCs. Here, based on ab initio molecular dynamics simulations and first‐principles density functional theory calculations, the interactions between oxygen, water, and surface defects of MAPbI3 are investigated. It is found that the photo‐oxidation of MAPbI3 concentrates on the surface of the crystal, and this degradation can be accelerated by surface iodine vacancy and moisture. When oxygen coadsorbs with water molecules or oxygen adsorbs at the iodine vacancy on the MAPbI3 surface, the energy levels of adsorbed O2 are significantly lowered, facilitating the photoexcited electron transfer and the formation of reactive superoxide anions (O2 − ). The understanding of the role of water and defects in MAPbI3 photo‐oxidation from this study paves the way for further optimization of stable perovskite solar cells. Abstract : The mechanism of water and surface vacancies facilitating photo‐oxidative degradation of methylammonium lead iodide perovskite is revealed. Water and surface vacancies lower the energy levels of oxygen, thus promoting the formation of reactive superoxide anions.